EFEKTIVITAS INTERVENSI BRISK WALKING: LITERATURE REVIEW - Dwi Esti Handayani; Kadek Ayu Erika; Andi Masyitha Irwan (Universitas Islam Negeri Alauddin Makassar, 2020)
Introduction: Physical inactivity and sedentary behavior contribute greatly to an increase in the burden of non-communicable diseases. One of the recommended exercises for increasing physical activity is brisk walking. This exercise is more accessible and acceptable than other forms of physical activity training. Methods: Literature search was conducted on 4 database; PubMed, Scopus, ScienceDirect and ProQuest. Articles reported in English for the last 5 years, brisk walking related to various health problems in patients and article published in randomized control trial. Results: A total of 729 articles were supported from four database searches and only 9 articles met the inclusion criteria. Some of the benefits that have proven to be effective evidence-based are to reduce fatigue levels especially in patients with breast cancer undergoing chemotherapy and high-level industrial workers. Effectively controlling blood pressure and reducing other cardiovascular risks. Other effectiveness such as prevention of postural disorders and reducing the risk of falling, increasing the ability and endurance to walk (exercise tolerance) by up to 45%. The effects of using brisk walking has it has to 2 months to 6 months after exercise. Conclusion The benefits of this exercise are primarily in reducing cardiovascular risk (including hypertension and blood sugar levels). This exercise is also recommended for anyone and is not required to be performed at home.ABSTRAKPendahuluan: Ketidakaktifan fisik dan perilaku menetap (Sedentary Behavior) berkontribusi besar pada peningkatan beban penyakit tidak menular. Salah satu latihan yang direkomendasikan untuk meningkatkan aktivitas fisik adalah brisk walking (jalan cepat). Latihan ini lebih mudah diakses dan diterima dibandingkan bentuk latihan aktivitas fisik lainnya. Metode: Pencarian literatur dilakukan pada 4 database; PubMed, Scopus, ScienceDirect dan ProQuest. Artikel yang dilaporkan dalam bahasa Inggris selama 5 tahun terakhir, brisk walking terkait dengan berbagai masalah kesehatan pada pasien dan artikel yang diterbitkan dalam uji kontrol acak (Randomized Control Trial). Hasil: Sebanyak 729 artikel yang diidentifikasi dari ke empat pencarian database dan hanya 9 artikel yang memenuhi kriteria inklusi. Berdasarkan 9 artikel yang telah dianalisis, beberapa manfaat yang telah terbukti efektif berdasarkan evidence based adalah untuk mengurangi tingkat kelelahan terutama pada pasien dengan kanker payudara yang menjalani kemoterapi dan pekerja industri tingkat tinggi. Efektif mengontrol tekanan darah dan mengurangi risiko penyakit kardiovaskular lainnya. Efektivitas lain seperti mencegah penurunan stabilitas postural dan mengurangi risiko jatuh, meningkatkan kemampuan keseimbangan dan daya tahan berjalan (toleransi olahraga) hingga 45%. Efek penggunaan brisk walking setidaknya menunjukkan efektivitas pada 2 bulan hingga 6 bulan setelah latihan. Kesimpulan: Manfaat latihan ini terutama pada pengurangan risiko kardiovaskular (termasuk hipertensi dan kadar gula darah). Latihan ini juga dianjurkan bagi siapa saja dan direkomendasikan untuk dapat dilakukan di rumah.